Composite material for electrical contacts and method for producing same
Patent Information
- Application Number
- JP2023544494
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-23
- Filing Date
- 2021-11-24
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2041-11-24
AI Technical Summary
【0021】 本発明の電気接点材は、電気接点で高い割合を占めるAg含有量を大きく低減して経済性を確保することができ、低いAg含有量にもかかわらず、電気接点材として要求される機械的、電気的および熱的特性を満足させることができる。また、従来化学的方法で製造する製造工程の複雑性および大量生産の問題点を改善することによって、電力機器製品のコスト節減を実現することができる。
Smart Images

Figure 0007631540000008 
Figure 0007631540000009 
Figure 0007631540000010
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrical contact material, which is a contact element that plays a role in conducting or interrupting the flow of an electric circuit, and to an electrical contact composite (or electrical contact material) and a method for manufacturing the same, and to an invention that can be used to manufacture a variety of application products for power equipment products (contactors, switches, circuit breakers, etc.). [Background technology]
[0002] Electrical contacts are contact elements that make or break the flow of an electrical circuit in a product. Such electrical contacts are widely used in power equipment products such as contactors, switches, circuit breakers, relays, and switches.
[0003] Electrical contacts require excellent thermal and electrical conductivity properties for electrical conduction, as well as a high melting point and thermally stable properties to minimize shape damage and fusion caused by arcs during electrical interruption.
[0004] Electrical contact materials are based on silver (Ag) materials with excellent electrical conductivity, and include AgCdO, AgSnO 2 In the case of electromagnetic contactors, which are electric power equipment products in the domestic power distribution industry, AgCdO-based electrical contacts containing environmentally regulated elements are used. In the case of circuit breakers, AgCdO-based electrical contacts are used in some cases, and AgWC-, AgC-, or AgNiC-based electrical contacts are used. In the case of electromagnetic contactors, which are electric power equipment products in the power distribution industry outside of Korea, AgCdO-based, AgSnO-based, or AgSnO-based electrical contacts are used depending on the country of use. 2 In the case of circuit breakers, AgWC, AgC, and AgNiC electrical contacts are used.
[0005] Electrical contacts applied in the power distribution industry account for a high cost portion of the final product. This is because the raw material used for electrical contacts is based on silver (Ag), a precious metal material. As it is a precious metal material, it is generally in a high price range, and fluctuations in the price of silver directly affect the price of electrical contacts. Generally, AgCdO-based and AgSnO-based electrical contacts are provided by electrical contact manufacturers both in Korea and overseas. 2 Looking at the silver content in Ag, AgC, and AgNiC electrical contacts, it accounts for approximately 80% or more, as shown in Table 1 below.
[0006] [Table 1]
[0007] As a result, electrical contact manufacturers are currently making great efforts and development efforts to reduce the high Ag content while maintaining the properties of electrical contacts by utilizing new technologies, new processes, and new materials. Summary of the Invention [Problem to be solved by the invention]
[0008] The object of the present invention is to solve the problems described above, and to provide a composite material for electrical contacts that has an optimal composition and composition ratio that satisfies the mechanical properties, electrical properties, and thermal properties required of an electrical contact material while reducing the Ag content in the electrical contact material, and a method for manufacturing the composite material for electrical contacts. [Means for solving the problem]
[0009] In order to achieve the above object, the composite material for electrical contacts of the present invention comprises silver (Ag) powder; a metal-based powder; and an Ag / C composite powder containing silver (Ag) and a carbon-based nanofiller.
[0010] In a preferred embodiment of the present invention, the metal-based powder may contain one or more selected from nickel (Ni), tungsten (W) and tungsten carbide (WC).
[0011] In a preferred embodiment of the present invention, the Ag / C composite powder is a material in which carbon nanofillers are inserted and dispersed inside Ag powder to integrate it, and has a density of 8.40 to 9.50 g / cm 3 may be also possible.
[0012] In a preferred embodiment of the present invention, the composite material for electrical contacts of the present invention may contain 60 to 70% by weight of the silver powder, 1 to 5% by weight of the Ag / C composite powder, and the balance of the metal-based powder.
[0013] In a preferred embodiment of the present invention, the composite material for electrical contacts of the present invention may be a processed product obtained by sintering, rolling, or extruding the above-mentioned composite material.
[0014] In a preferred embodiment of the present invention, the processed composite material has a density of 9.550 to 9.950 g / cm 3 and may have an electrical conductivity of 46 to 52% IACS and a Vickers hardness of 91.0 to 95.0 HV.
[0015] In a preferred embodiment of the present invention, the processed composite material can satisfy the following thermal conductivity measurements: 230.0 to 285.0 W / (m·K) at 25°C, 230.0 to 280.0 W / (m·K) at 40°C, 225.0 to 275.0 W / (m·K) at 60°C, 220.0 to 270.0 W / (m·K) at 80°C, and 215.0 to 265.0 W / (m·K) at 90°C.
[0016] Yet another object of the present invention relates to a method for producing the composite material for electrical contacts, which can include the steps of: mixing silver (Ag) powder, a metal-based powder, and an Ag / C composite powder containing silver (Ag) and a carbon-based nanofiller to produce a mixed powder; sintering, rolling, or extruding the mixed powder to produce a workpiece; and heat-treating the workpiece.
[0017] In a preferred embodiment of the present invention, the Ag / C composite powder may be produced by carrying out a process including the steps of mixing Ag powder and a carbon-based nanofiller, followed by low-energy milling to produce a mixture, and subjecting the low-energy milled mixture to high-energy milling.
[0018] In a preferred embodiment of the invention, the low energy milling and high energy milling can be performed independently by attrition milling, planetary milling, jet milling, or disc milling.
[0019] In a preferred embodiment of the present invention, the low energy milling can be performed by attrition milling at 100 to 200 rpm for 1 to 60 minutes.
[0020] In a preferred embodiment of the present invention, the high-energy milling can be performed as attrition milling at 400 to 600 rpm for 4 to 24 hours. Effect of the Invention
[0021] The electrical contact material of the present invention can ensure economy by significantly reducing the Ag content, which is a high proportion in electrical contacts, and can satisfy the mechanical, electrical and thermal properties required for an electrical contact material despite the low Ag content. In addition, the cost reduction of power equipment products can be achieved by improving the complexity of the manufacturing process and the problems of mass production in the conventional chemical method. [Brief description of the drawings]
[0022] FIG. 1 shows the measurement results of the densities of the Ag / C composite powder and the Ag powder produced in Preparation Example 1. FIG. 2a is an SEM measurement image of the Ag powder, and FIG. 2b is an SEM measurement image of the Ag / C composite powder produced in Preparation Example 1. FIG. 3 shows the measurement results of particle size change of the Ag powder and the Ag / C composite powder produced in Preparation Example 1. FIG. 4 shows the results of thermogravimetric analysis of the Ag / C composite powder produced in Preparation Example 1. FIG. 5 shows the results of measurements of electrical conductivity and hardness as a function of the Ag:Ni ratio in the electrical contacts carried out in Experimental Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] Hereinafter, the present invention will be described in detail through a method for producing a composite material for electrical contacts (or an electrical contact material) of the present invention.
[0024] The present invention relates to a composite material for electrical contacts, which is manufactured using a composition incorporating Ag / C composite powder manufactured by a specific method in order to reduce the Ag content in the electrical contact material.
[0025] The composite material for electrical contacts of the present invention can also be provided in the form of a mixed powder in which the composite material composition for electrical contacts is mixed.
[0026] In addition, the composite material for electrical contacts of the present invention can be provided in the form of a processed product having a fixed shape, rather than a powder type, by carrying out a process including: step 1 of mixing the composite material composition for electrical contacts to produce a mixed powder; step 2 of processing the mixed powder to produce a processed product; and step 3 of heat-treating the processed product.
[0027] Also, the method may further include a fourth step of cutting the workpiece heat-treated in the three steps.
[0028] First, the composite material for electrical contacts in the first stage will be described.
[0029] The composite material (or composition) for electrical contacts includes Ag powder, metal-based powder, and Ag / C composite powder.
[0030] The content of Ag powder in the composite for electrical contacts is 60 to 70 wt % of the total weight of the composition, preferably 60.0 to 67.0 wt %, and more preferably 62 to 65 wt %. In this case, if the Ag powder content is less than 60 wt %, the composite for electrical contacts may have a problem of having too low electrical conductivity, while if the Ag powder content exceeds 70 wt %, the effect of reducing the amount of Ag used in the composite for electrical contacts is insufficient to ensure economic efficiency, and there may be a problem of the hardness being too low, so it is better to use it within the above range.
[0031] It is also preferable to use Ag powder with a particle size of 200 μm or less, preferably 5 to 120 μm, and more preferably 5 to 50 μm. If the particle size of the Ag powder exceeds 200 μm, it may not be mixed sufficiently with other powders in the composition, and other components than Ag may not be distributed uniformly in the electrical contact material. Therefore, it is better to use Ag powder with a particle size in the above range.
[0032] Next, the metal-based powder is used to improve mechanical properties such as wear resistance of the electrical contact, and may contain one or more selected from nickel (Ni), tungsten (W), and tungsten carbide (WC), and may preferably contain one or more selected from nickel and tungsten. The content of the metal-based powder in the composition is the remaining amount in 100% by weight of the composition excluding the Ag powder and Ag / C composite powder.
[0033] Next, the Ag / C composite powder is a material in which carbon-based nanofillers are inserted and dispersed inside Ag powder, and may be manufactured by the following method.
[0034] The Ag / C composite powder can be produced by mixing Ag powder and a carbon-based nanofiller, followed by low-energy milling to produce a mixture in one step, and then high-energy milling the low-energy milled mixture in a second step.
[0035] The mixture in the first step of the method for producing Ag / C composite powder is a dry mixture of Ag powder and carbon nanofiller, and may contain 1-5% by weight of the carbon nanofiller and the remaining Ag powder, preferably 2-5% by weight of the carbon nanofiller and the remaining Ag powder, more preferably 2.5-4.0% by weight of the carbon nanofiller and the remaining Ag powder. In this case, if the carbon nanofiller content is less than 1% by weight, the mechanical properties of the electrical contact material produced using the Ag / C composite powder are insufficient, and if the carbon nanofiller content exceeds 5% by weight, the electrical contact material has excellent mechanical properties but too low electrical conductivity, so it is better to use it within the above range.
[0036] The Ag powder to be used has a particle size of 200 μm or less, preferably 5 to 120 μm, and more preferably 5 to 50 μm.
[0037] The carbon nanofiller may include one or more selected from single-walled carbon nanotubes (CNTs), multi-walled carbon nanotubes, and graphene, preferably one or more selected from single-walled CNTs and multi-walled CNTs, and more preferably multi-walled CNTs, and more preferably a CNT having a purity of 85 to 95% and a density of 1.20 to 1.40 g / cm. 3 Multi-walled CNTs of the above type can be used.
[0038] The low-energy milling in one step is performed to uniformly disperse the carbon-based nanofiller on the surface of the Ag powder, and the low-energy milling can be performed by attrition milling, planetary milling, jet milling, or disc milling, and preferably, attrition milling can be performed.
[0039] When the low energy milling is carried out by attrition milling, it is preferably carried out at 100 to 200 rpm for 1 to 60 minutes, preferably at 100 to 180 rpm for 1 to 50 minutes, and more preferably at 100 to 160 rpm for 1 to 40 minutes.
[0040] The second step involves high-energy milling of the mixture that was subjected to low-energy milling, and inserting the carbon-based nanofillers dispersed on the surface of the Ag powder into the interior of the Ag powder to produce an integrated material (Ag / C composite powder).
[0041] The high energy milling can be performed by attrition milling, planetary milling, jet milling or disk milling, and preferably by attrition milling.
[0042] In addition, when the high energy milling is performed by attrition milling, it is better to perform it under the condition of 400 to 600 rpm for 4 to 24 hours, preferably under the condition of 400 to 550 rpm for 4 to 20 hours, and more preferably under the condition of 400 to 500 rpm for 4 to 16 hours. In this case, if the rpm is less than 400 or the milling time is less than 4 hours, there may be a problem that the carbon-based nanofiller is not inserted into the Ag powder as the base material in many cases, and if the rpm exceeds 600, there may be a problem that the morphology of the Ag / C composite powder is not uniform, and if the milling time exceeds 24 hours, it is uneconomical, so it is better to perform the high energy milling under the above conditions.
[0043] The Ag / C composite powder thus produced has a particle size similar to that of the Ag powder used in the production, but has a lower density. More specifically, the density of the Ag powder is about 10.1 to 10.4 g / cm. 3 Although it varies depending on the carbon nanofiller, the Ag / C composite powder made with multi-walled CNTs has a density of 8.40 to 9.50 g / cm 3 , preferably 8.40 to 9.35 g / cm 3 , more preferably 8.45 to 9.20 g / cm 3 may be also possible.
[0044] Next, in the second step, the mixed powder produced in the first step is sintered, rolled or extruded to produce a composite material for electrical contacts depending on its application and shape (e.g., plate, wire, strip, rivet shape) to produce a workpiece.
[0045] The third step is a step of heat-treating the processed product. The heat treatment is carried out according to the purpose of use to improve the physical properties. The heat treatment can be carried out by a heat treatment method and conditions generally used in the art. In a preferred example, the heat treatment can be carried out in an inert atmosphere at 300 to 500°C for 1 to 2 hours. 2When heat treatment is performed in an inert atmosphere such as a fluorine-containing gas, the carbon-based nanofiller does not become carbonized even at high temperatures, so the heat treatment must be performed in an inert atmosphere.
[0046] Also, the heat-treated workpiece can be cut into a desired shape and size to produce a final electrical contact product.
[0047] The composite material for electrical contacts of the present invention may contain 0.02 to 0.90% by weight, preferably 0.04 to 0.65% by weight, and more preferably 0.04 to 0.40% by weight of a carbon nanofiller based on the total weight of the composite material.
[0048] The composite material for electrical contacts of the present invention in the form of a processed product has a density of 9.550 to 9.840 g / cm 3 Preferably, the density is 9.600 to 9.830 g / cm 3 More preferably, the density is 9.650 to 9.800 g / cm 3 may be also possible.
[0049] Furthermore, the composite material for electrical contacts in the processed product form of the present invention may have an electrical conductivity of 46 to 52% IACS (The International Annealed Copper Standard), preferably an electrical conductivity of 46 to 50% IACS, and more preferably an electrical conductivity of 46.5 to 48.5% IACS.
[0050] Furthermore, the composite material for electrical contacts in the processed product form of the present invention may have a Vickers hardness of 91.0 to 95.0 HV, preferably 91.5 to 95.0 HV, and more preferably 91.5 to 94.5 HV.
[0051] Furthermore, the composite material for electrical contacts in the processed product form of the present invention can satisfy, when the thermal conductivity is measured, 230.0 to 285.0 W / (m·K) at 25°C, 230.0 to 280.0 W / (m·K) at 40°C, 225.0 to 275.0 W / (m·K) at 60°C, 220.0 to 270.0 W / (m·K) at 80°C, and 215.0 to 265.0 W / (m·K) at 100°C, and preferably 234.0 to 283.0 W / (m·K) at 25°C, 234.0 to 278.0 W / (m·K) at 40°C, It can satisfy 230.0 to 274.0 W / (m·K) at 60°C, 224.0 to 270.0 W / (m·K) at 80°C, and 222.0 to 265.0 W / (m·K) at 100°C, and more preferably 242.0 to 282.0 W / (m·K) at 25°C, 238.0 to 277.0 W / (m·K) at 40°C, 235.0 to 274.0 W / (m·K) at 60°C, 232.0 to 268.0 W / (m·K) at 80°C, and 228.0 to 262.0 W / (m·K) at 100°C.
[0052] The present invention will be described in more detail below with reference to examples. However, it should be understood that the following examples are not intended to limit the scope of the present invention, but are merely intended to aid in the understanding of the present invention.
[0053] [Example] Preparation Example 1: Production of Ag / C composite powder Ag powder with a particle size of 63 μm or less (density 10.2 g / cm 3 , Tap density 1.7~1.8g / cm 3 ) and multi-walled carbon nanotubes (purity 90%, density 1.3 g / cm3) as carbon nanofillers. 3 , MWCNT) were prepared.
[0054] Next, 97 wt % of the Ag powder and 3 wt % of the MWCNT were dry mixed and then attrition milled at about 120 to 150 rpm for 10 minutes to produce a mixture in which the MWCNT was uniformly dispersed on the surface of the Ag powder.
[0055] Next, the mixture was subjected to attrition milling at about 400~450 rpm for 10 hours, and then the frictional heat generated during the milling process was cooled and stabilized to obtain Ag / C composite powder in which MWCNTs were dispersed and inserted into the Ag powder base material.
[0056] (1) Measurement of Tap density The density of the produced Ag / C composite powder was 9.02 g / cm 3 and the tap density is 3.0 g / cm 3 As shown in Figure 1, the Tap density is much higher than that of Ag powder because the Ag powder became solid and dense through high-energy milling, and the density is lower because the MWCNTs are inserted and integrated into the Ag powder.
[0057] (2) Measurement of SEM images Moreover, SEM images of the Ag powder and the produced Ag / C composite powder are shown in Figure 2, A and B. A is an image of the Ag powder, and B is an image of the Ag / C composite powder.
[0058] Referring to Figure 2A, it can be seen that the Ag powder has an irregular particle shape and is concentrated in large numbers. In contrast, referring to Figure 2B, it can be seen that the Ag / C composite powder has a shape that is close to a sphere overall. In addition, no MWCNTs are found on the surface of the Ag / C composite powder, which means that the MWCNTs are completely inserted and dispersed inside the Ag powder.
[0059] Through this, it was confirmed that Ag / C composite powder can be produced economically through a mechanical process, not through complicated chemical processes.
[0060] (3) Measurement of particle size change In addition, the particle size changes of the Ag powder and the produced Ag / C composite powder were measured, and the results are shown in FIG.
[0061] Comparing the particle size of Ag powder and Ag / C composite powder before and after high-energy milling, it can be seen that +25um and -25um account for more than 90% of the total particle size of Ag powder. In contrast, it can be seen that -25um accounts for more than 90% of the Ag / C composite powder. The actual particle size of Ag powder is manufactured to be 25um or less, but since it is gathered during the manufacturing process, it appears that Ag powder with a particle size of +25um is manufactured. It was found that the Ag / C composite powder manufactured through high-energy milling has reduced powder with a particle size of +25um or more because the particles are separated from each other during the high-energy milling process and the CNTs are inserted and dispersed into the particles and gathered tightly.
[0062] (4) Thermogravimetric analysis (TGA, Thermogravimetric analyzer) In order to confirm whether the carbon-based nanofiller was contained in the Ag / C composite powder, the change in weight with temperature was measured under the condition of adding oxygen, and the results are shown in Figure 4.
[0063] Referring to Figure 4, as the temperature increases, the carbon nanofiller contained in the Ag / C composite powder disappears due to reaction with the internal conditions. In this process, only the carbon nanofiller inserted at 100% of the initial weight is removed, and the final remaining weight can be confirmed. Through this change in weight, it was confirmed that the MWCNTs were inserted and dispersed in Ag in the Ag / C composite powder produced.
[0064] Preparation example 2 The Ag / C composite powder was produced by performing low-energy and high-energy milling in the same manner as in Preparation Example 1, but using 95 wt % Ag powder and 5 wt % MWCNT, as shown in Table 2 below.
[0065] Preparation example 3 The Ag / C composite powder was produced by performing low-energy and high-energy milling in the same manner as in Preparation Example 1, but using single-walled CNTs instead of multi-walled CNTs, and the Ag / C composite powder was produced using 95 wt % Ag powder and 3 wt % single-walled CNTs as shown in Table 2 below.
[0066] [Table 2]
[0067] Experimental example 1: Setting the appropriate Ag, Ni ratio Ag powder with a particle size of 63um or less (density 10.2g / cm 3 , Tap density 1.7~1.8g / cm 3 Mixtures were prepared by varying the mixing ratio of ZnO powder and Ni powder with a particle size of 45 μm or less, and then the mixtures were made into bulk billets and extruded.
[0068] The extruded workpiece was then placed in an inert atmosphere (N 2 After heat treatment at about 400°C in a vacuum atmosphere, the plate was cut to produce a plate-shaped electrical contact.
[0069] In addition, the electrical conductivity (%IACS) and Vickers hardness (Hv) of each of the electrical contacts manufactured with different mixing ratios were measured, and the results are shown in FIG.
[0070] Referring to FIG. 5, it can be seen that electrical contacts containing Ag in the range of about 60 to 70 wt % have electrical conductivity of 50% IACS or more while satisfying hardness of 100 Hv or more.
[0071] Through this, it was confirmed that the appropriate Ag content when manufacturing electrical contacts using Ag and Ni is about 60 to 70 wt %. In order to derive a method to further reduce the Ag content while still satisfying this range, the amounts of Ag powder and Ag / C composite powder used were designed in various ways, and composite materials for electrical contacts were manufactured according to the following examples.
[0072] Example 1: Manufacturing of composite material (processed product) for electrical contacts Ag powder with a particle size of 63um or less (density 10.2g / cm 3 , Tap density 1.7~1.8g / cm 3 ), Ni powder having a particle size of 45 μm or less, and the Ag / C composite powder produced in Preparation Example 1 were each prepared, and then these were mixed to produce a mixture.
[0073] The mixture was then fabricated into a bulk billet and then extruded.
[0074] The extruded workpiece was then placed in an inert atmosphere (N 2 After heat treatment at 300° C. in a 350° C. atmosphere, the plate was cut to produce a plate-shaped electrical contact.
[0075] Examples 2 to 5 and Comparative Example 1 Composite materials for electrical contacts were manufactured in the same manner as in Example 1, but the contents of Ag powder and the Ag / C composite powder of Preparation Example 1 were varied as shown in Table 3 below, to manufacture the composite materials for electrical contacts, and Examples 2 to 4 and Comparative Example 1 were carried out.
[0076] However, in Example 5, the Ag / C composite powder of Preparation Example 3 was used instead of Preparation Example 1.
[0077] [Table 3]
[0078] Comparative Example 2 An AgCdO electrical contact material with an Ag content of 80 wt % was prepared.
[0079] Comparative Example 3: Production of composite material for electrical contacts via chemical synthesis An alloy containing 65 wt % Ag and 35 wt % Ni was mixed with Ag-coated carbon nanotubes to prepare a powder mixture as follows.
[0080] 0.04 g of carbon nanotubes was dissolved in 7 M nitric acid (HNO 3) solution, and ultrasonic dispersion and acid treatment were performed for 5 minutes and 2 hours, respectively.
[0081] Thereafter, the ultrasonically dispersed and acid-treated carbon nanotubes were washed with deionized water to a pH of 7 using vacuum filtration.
[0082] The washed carbon nanotubes were then treated with tin chloride (SnCl 2 ) and hydrochloric acid (HCl) mixed solution and paraffinum chloride (PdCl 2 ) and hydrochloric acid (HCl) in a mixed solution, and ultrasonic waves were applied to remove tin (Sn 2+ ) and palladium (Pd 2+ ) was attached to the surface of carbon nanotubes.
[0083] Then, 0.3 M silver nitrate (AgNO 3 The tin and palladium-bonded carbon nanotubes were added to the aqueous solution and mixed until the solution became colorless.
[0084] Then, 0.1M glyoxylic acid solution and 0.5M sodium hydroxide (NaOH) solution were mixed until the pH reached 9, and the mixed solution was reacted at 90°C for 1 hour, and then washed with deionized water using a vacuum filtration method until the pH reached 7, producing silver-coated carbon nanotubes.
[0085] The Ag-coated carbon nanotubes and the alloy were then mixed to produce a powder mixture.
[0086] Thereafter, the powder mixture was ultrasonically dispersed and vacuum dried, and then the vacuum dried powder mixture was sintered to produce an electrical contact composite. At this time, the powder mixture was sintered at a temperature of 750°C to 830°C for 1 minute while maintaining the temperature, and the sintering method used was spark plasma sintering (SPS).
[0087] Experimental example 2: Measurement of electrical, mechanical, and thermal properties The density, electrical conductivity, Vickers hardness and thermal conductivity of the electrical contacts of Examples 1 to 5 and Comparative Examples 1 to 3 were measured, and the results are shown in Table 4 below.
[0088] [Table 4]
[0089] Referring to Table 4, it was confirmed that the electrical contacts of the present invention manufactured by a mechanical method in Examples 1 to 5 exhibited electrical properties and thermal properties in a similar range to that of Comparative Example 1, which is a conventional commercial product, despite the low Ag content. In addition, Comparative Example 3, which is an electrical contact manufactured by a conventional chemical method, exhibited excellent electrical properties and hardness, but showed slightly inferior thermal properties compared to Examples 1 to 4.
[0090] In addition, the electrical contacts of Examples 1 to 4, which were manufactured using multi-walled CNTs, showed relatively better thermal properties than Example 5, which used single-walled CNTs.
[0091] Experimental example 3: Electrical life measurement After manufacturing electrical contacts for switches using the electrical contact composites of Example 2, Comparative Example 2, and Comparative Example 3, the electrical contacts were applied to the products, and tests were performed by connecting loads using wires that meet the product specifications. At this time, the test current and conditions were as shown in Table 5, and 6 times the current was applied to count the number of on-off switches of the products to measure the electrical lifespan, and the results are shown in Table 6 below.
[0092] [Table 5]
[0093] [Table 6]
[0094] Referring to the electrical life measurement results, it was confirmed that the electrical contacts made of only Ag and Ni had very poor electrical life. Also, it was confirmed that the electrical contacts of AgCdO (Comparative Example 2), which is a conventional cadmium-based electrical contact material, and Comparative Example 3, which is an electrical contact material made by a chemical method, had electrical life that was 8 to 10% lower than that of the present invention.
[0095] Example 6 A composite material (processed product) for electrical contacts was manufactured in the same manner as in Example 1, using Ni powder at a fixed content of 35% by weight and adjusting the content of Ag powder and the Ag / C composite powder manufactured in Preparation Example 2.
[0096] In addition, the content of multi-walled CNTs in the prepared composite material for electrical contacts is as shown in Table 7 below, and the electrical conductivity and Vickers hardness of the prepared composite material for electrical contacts (processed product) are also shown in Table 7.
[0097] [Table 7]
[0098] Referring to Table 7, it can be seen that when the content of CNT, which is a carbon-based nanofiller in the electrical contact composite, is 0.9 wt%, the hardness is excellent, but the electrical conductivity is low at 50% IACS, which is a problem. From Table 6, it can be seen that using the carbon nanofiller in an amount of 0.02 to 0.90 wt%, preferably 0.04 to 0.65 wt%, and more preferably 0.04 to 0.40 wt%, based on the total weight of the composite, is advantageous from the standpoint of ensuring appropriate electrical properties and mechanical properties.
[0099] Based on the above examples and experimental examples, it was confirmed that the electrical contact composite of the present invention is a material that satisfies the electrical, mechanical and thermal properties required for an electrical contact material while reducing the Ag content, which is expensive in electrical contacts. Such an electrical contact composite of the present invention can be applied to various power equipment products such as contactors, switches and circuit breakers.
[0100] Although the preferred embodiment and examples of the present invention have been described above, it is clear that the present invention can use various changes, modifications and equivalents, and that the above embodiment and examples can be appropriately modified and applied in the same manner. Therefore, the above description should not be construed as limiting the scope of the present invention, which is defined by the limits of the following claims.
Claims
1. Silver (Ag) powder; A metal-based powder containing at least one selected from nickel (Ni), tungsten (W) and tungsten carbide (WC); and A composite material for electrical contacts comprising: an Ag / C composite powder containing silver (Ag) and a carbon-based nanofiller and having a density of 8.40 to 9.50 g / cm 3 ; The Ag / C composite powder is a material in which carbon nanofillers are inserted and dispersed inside Ag powder, The carbon-based nanofiller includes at least one selected from the group consisting of single-walled carbon nanotubes (CNTs), multi-walled carbon nanotubes, and graphene; The composite material for electrical contacts is characterized in that, when thermal conductivity is measured, it satisfies 225.0 to 275.0 W / (m·K) at 60°C, 220.0 to 270.0 W / (m·K) at 80°C, and 215.0 to 265.0 W / (m·K) at 100°C.
2. 2. The composite material for electrical contacts according to claim 1, comprising 60 to 70% by weight of said silver powder, 1 to 5% by weight of said Ag / C composite powder, and the balance of said metal-based powder.
3. A composite material for electrical contacts, comprising a processed product obtained by sintering, rolling or extruding the composite material for electrical contacts described in claim 1 or 2.
4. Density: 9.550 to 9.840 g / cm 3 and 4. The composite material for electrical contacts according to claim 3, characterized in that it has an electrical conductivity of 46 to 52% IACS and a Vickers hardness of 91.0 to 95.0 HV.
5. 4. The composite material for electrical contacts according to claim 3, characterized in that, when thermal conductivity is measured, it satisfies 230.0 to 285.0 W / (m·K) at 25° C. and 230.0 to 280.0 W / (m·K) at 40° C.
6. Mixing silver (Ag) powder, metal-based powder, and Ag / C composite powder containing silver (Ag) and carbon-based nanofiller to prepare a mixed powder; sintering, rolling or extruding the mixed powder to produce a workpiece; and heat treating the workpiece; The metal-based powder includes at least one selected from nickel (Ni), tungsten (W) and tungsten carbide (WC); The Ag / C composite powder is a material in which carbon nanofillers are inserted and dispersed inside Ag powder, and the Ag / C composite powder has a density of 8.40 to 9.50 g / cm 3 and The carbon-based nanofiller includes at least one selected from the group consisting of single-walled carbon nanotubes (CNTs), multi-walled carbon nanotubes, and graphene; The Ag / C composite powder is produced by the steps of: mixing Ag powder and a carbon-based nanofiller, and then subjecting the mixture to low-energy milling; and subjecting the mixture obtained by low-energy milling to high-energy milling.
7. 7. The method of claim 6, wherein the low energy milling and the high energy milling are independently performed by attrition milling, planetary milling, jet milling, or disc milling.
8. The low energy milling is performed by attrition milling at 100 to 200 rpm for 1 to 60 minutes, 7. The method for producing a composite material for electrical contacts according to claim 6, wherein the high energy milling is performed by attrition milling at 400 to 600 rpm for 4 to 24 hours.
Citation Information
Patent Citations
Electrical contact material and method for producing the same
JP2015105439A
Silver-carbon based electrical contact material for circuit breaker and method for preparing thereof
KR1020150103569A